Linguistic emancipation within the Serbian mental map: The implementation of the Montenegrin and Macedonian standard languages - Voß, Christian (Aegean Working Papers in Ethnographic Linguistics, 2019)
This paper explores the striking similarity in the hesitant implementation of the new Macedonian and Montenegrin standards, which has taken unusually long in both cases. As will be shown, a comparative look at the two standardisation processes reveals parallels of language politics in Macedonia after 1944 and Montenegro after 2006. In both cases the implementation of the new standard is hesitant, slow, and shows policy shifts. A key conclusion of this paper is that this normative vacuum is possible because Serbian, as the traditional H-variety, is omnipresent in both countries. This observation however implies an optimistic outlook for Montenegrin since Macedonian standardisation today can be assessed as a success story, despite continuous contestation from neighbouring countries. The paper focuses on both differences and commonalities of the standardisation process in these two Yugoslav successor states.